Pengembangan Aplikasi Exampro Sebagai Model Evaluasi Pembelajaran Berbasis Digital - Ashadi, Ninik Rahayu (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this Study is to find out How the development of the Exampro app as a digital-based learning evaluation model resulted. The method of this study is This research uses a Research and Development/R&D approach with a modified Borg & Gall model of development. This model consists of ten steps, however in this study it is simplified to six main stages, namely: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product testing. Research Results (1) based on the validation assessment of the Subject Matter Expert showed a feasibility score of 88%, falling into the "Very Good" category. The experts assessed the content of the evaluation material on the application already relevant to the prevailing principles of learning evaluation and curriculum. Media Expert Validation earned a score of 85%, also in the "Very Good" category. The user interface was assessed as intuitive, functional, and in accordance with the principles of digital media design, (2) comparison of the results of each stage of validation and testing. All scores were in the range of 8288%, signifying that the ExamPro app was generally feasible and effectively used as a model of digital-based learning evaluation (3) students in small group examinations, which were asked to use the app in examination simulation. The questionnaire results showed an average satisfaction score of 82%. Students felt it was easier to access and complete the evaluation using this system compared to the conventional paper-based method.Based on the results of the study it can be concluded the development of the Exampro app as a digital-based learning evaluation model using the Borg & Gall development model of validation and comparison has been tested. try. The whole score was in the range of 8288%, signifying that the ExamPro app was generally feasible and effectively used as a digital-based learning evaluation model.